Acute liver damage and ecstasy ingestion. Issue 3 (March 1996) - Ellis, A J; Wendon, J A; Portmann, B; Williams, R
Abstract : Eight cases of ecstasy related acute liver damage referred to a specialised liver unit are described. Two patients presented after collapse within six hours of ecstasy ingestion with hyperthermia, hypotension, fitting, and subsequently disseminated intravascular coagulation with rhabdomyolysis together with biochemical evidence of severe hepatic damage. One patient recovered and the other with evidence of hyperacute liver failure was transplanted but subsequently died, histological examination showing widespread microvesicular fatty change. Four patients presented with acute liver failure without hyperthermia. All four fulfilled criteria for transplantation, one died before a donor organ became available, and two died within one month post-transplantation of overwhelming sepsis. Histological examination showed submassive lobular collapse. Two patients presented with abdominal pain and jaundice and recovered over a period of three weeks; histological examination showed a lobular hepatitis with cholestasis. Patients developing jaundice or with evidence of hepatic failure particularly encephalopathy and prolongation of the international normalised ratio, or both, whether or not preceded by hyperthermia, should be referred to a specialised liver unit as liver transplantation probably provides the only chance of recovery.